Pencegahan Hipertensi pada Lansia melalui Edukasi Kesehatan di Posyandu Lansia Desa Rejasari Purwokerto Barat - Nur Rifka Zaneta; Nisa Sifa Fitria; Nurul Tri Agustina; Nyoman Triana Sari; Puput Dwi Agustianingsih; Putri Estiana Anggraini; Khamdiyah Indah (Institut Nalanda, 2026)
Hypertension is a non-communicable disease with a high incidence rate and is a major factor that increases the risk of cardiovascular diseases. The lack of public awareness, especially in rural areas, regarding the prevention and control of hypertension has become a health issue that requires serious action. The purpose of this activity is to increase the knowledge of the community in Rejasari Village, Purwokerto Barat, regarding hypertension. The activity was conducted on November 22, 2025, involving 20 respondents. The method used in the implementation was community service activities thru health counseling, which included providing material on the understanding of hypertension, risk factors including signs and symptoms, and prevention efforts thru the application of a healthy lifestyle. Education was provided interactively using leaflets and question-and-answer discussions. The pre-test results showed that the community's knowledge was relatively low, with an average of correct answers reaching 61.5%. After the counseling, the post-test results indicated a significant improvement in knowledge, with an average score of 69.8%. This activity demonstrated that the community better understands the importance of adopting a healthy lifestyle daily to prevent hypertension. The program is expected to be a sustainable preventive and promotive effort in reducing the risk of hypertension in the Rejasari Village community.